Black Women and Female Abolitionists in Print - Moffatt, Kate; Sharren, Kandice (Romanticism on the Net)

(untitled) (Université de Montréal, 2020)
The WPHP Monthly Mercury is the podcast for the Women’s Print History Project, a bibliographical database that seeks to provide a comprehensive account of women’s involvement in print in a long Romantic period. The podcast provides us with an opportunity to develop in-depth analyses of our data. In the August 2020 episode, “Black Women and Female Abolitionists in Print,” the entire team of the WPHP joins hosts Kandice Sharren and Kate Moffatt to speak to the Black Women’s and Abolitionist Print History Spotlight Series published on the WPHP website between June 19 and July 31, 2020. The WPHP team cameos are followed by a discussion between the hosts about the common themes of the spotlights produced. We then analyze some of the common threads across the spotlights, including how the people, firms and titles featured were documented and framed within a predominantly white transatlantic print culture. We conclude by considering some strategies for working within the constraints of the resources that we rely on and adapting our own data model to be more transparent and inclusive. This textual supplement includes a description of the episode, links to all records in the WPHP database referenced in the episode, resources relevant to this topic, our works cited list, and suggestions for further reading.